Investigation on the effect of EDFA location in ring cavity Brillouin-Erbium fiber laser - Ahmad Hambali, Nor Azura Malini; Mahdi, Mohd Adzir; Al-Mansoori, Mohammed Hayder; Abas, Ahmad Fauzi; Saripan, M. Iqbal (Optical Society of America, 2009)
We have investigated the characteristics of Brillouin-Erbium fiber laser (BEFL) with variation of Erbium-doped fiber amplifier (EDFA) locations in a ring cavity configuration. Three possible locations of the EDFA in the laser cavity have been studied. The experimental results show that the location of EDFA plays vital role in determining the output power and the tuning range. Besides the Erbium gain, Brillouin gain also contributes to the performance of the BEFL. By placing the EDFA next to the Brillouin gain medium (dispersion compensating fiber), the Brillouin pump signal is amplified thereby generating higher intensities of Brillouin Stokes line. This efficient process suppresses the free running self-lasing cavity modes from oscillating in cavity as a result of higher Stokes laser power and thus provide a wider tuning range. At the injected Brillouin pump power of 1.6 mW and the maximum 1480 nm pump power of 135 mW, the maximum Stokes laser power of 25.1 mW was measured and a tuning range of 50 nm without any self-lasing cavity modes was obtained.